The LIFE CYCLE OF COVID-19 STAGES AND TREATMENT - Ripu Daman M. Singh; Nida Malim; Aves Raza Khan; Huda Khan; Nauman Khatib; Aakifah Gounda (Journal of Biomedical and Pharmaceutical Research, 2020)
The coronavirus disease 19 (COVID-19) is a highly transmittable and pathogenic viral infection caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)bat viruses, therefore bats could be the possible primary reservoir , which emerged in Wuhan, China and spread around the world. The intermediate source of origin and transfer to humans is not known, however, the rapid human to human transfer has been confirmed widely. There is no clinically approved antiviral drug or vaccine available to be used against COVID-19. However, few broad-spectrum antiviral drugs have been evaluated against COVID-19 in clinical trials, resulted in clinical recovery. We also discuss the approaches for therapeutic combinations to cope with this viral outbreak. Chloroquine has been sporadically used in treating SARS-CoV-2 infection. Hydroxychloroquine shares the same mechanism of action as chloroquine, but its more tolerable safety profile makes it the preferred drug to treat malaria and autoimmune conditions. We propose that the immunomodulatory effect of hydroxychloroquine also may be useful in controlling the cytokine storm that occurs late-phase in critically ill SARS-CoV-2 infected patients.